Evaluación de extractos vegetales en la germinación de semillas de arroz (oryzasativa), cultivar lp-5 en Yara, provincia Granma (Original) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The use of plant extracts as biostimulants in current agricultural production is increasing due to the polluting effects and high costs of industrially produced chemical agricultural inputs. The objective of this research is to evaluate four plant extracts in the rice seeds germination (Oryza sativa), cultivar LP-5. The experiment was developed in the Antonio Maceo Base Business Unit, Yara municipality, Granma province, belonging to the Fernando Echenique Agroindustrial Grain Company in September 2020. The treatments consisted of the preparation of three aqueous vegetable extracts of mulberry (Morus alba), willow (Salix babylonica), and a proportionate mixture of mulberry and willow extract, and a fourth treatment with only water as a control. In each of the four containers with the aforementioned treatments, 100 seeds were soaked for 48 hours, with three repetitions for each treatment. In each of the five containers with the aforementioned treatments, 100 seeds  were soaked for a time of 48 hours, with three replications for each treatment. The germinated seeds per day were counted non-cumulatively, in order to calculate the germination percentage in the six days. It was statistically processed through a completely randomized design with three repetitions using the Kruskal-Wallis test. The results showed that with the willow leaf extract, 96.0% of germinated seeds were reached in only six days, the rest of the treatments only reached 84.0%.
Keywords: rice; seeds; vegetable extracts